Connected Automated Driving: Civil Liability Regulation in the European Union - Shevchenko, Olga (Teisė, 2020)
The aim of this article is to provide with the option of civil liability regulation of connected autonomous vehicles (CAVs) and autonomous vehicles (AVs) at the European Union level in the light of introduction of Connected Automated Driving (CAD) on the common market.